"Among the Revolutions of Her Sex": The Biographies of Deborah Sampson Gannett and Mary Wollstonecraft Godwin. Issue 3 (2nd July 2016) - Smith, Abigail M.
ABSTRACT: In 1797, Herman Mann published The Female Review, or Memoirs of an American Young Lady, a biography depicting the embellished exploits of the cross-dressing soldier Deborah Sampson Gannett in the American War of Independence. With only a modest fear of reproach, Mann depicted a masculine, courageous Gannett whose "revolution of her sex"—becoming a soldier—was a significant and patriotic contribution to the fight for American independence. However, when in the following year William Godwin published his revealing Memoirs of the Author of A Vindication of the Rights of Woman about his deceased wife, Mary Wollstonecraft Godwin, her "revolution in female manners" became the ultimate cultural threat to female chastity and domestic sanctity. Godwin's naive idealism not only ruined the posthumous reputation of his wife, but also caused a conservative backlash against the general freedoms of women on both sides of the Atlantic. Mann's Female Review was similarly destructive to Gannett's reputation and, in 1802, Mann wrote a speech for Gannett to perform on a public speaking tour, in which she apologized for her behavior and revealed to the world that she had since adopted a domestic life. In this essay, it is suggested that the overwhelmingly negative reception of Godwin's Memoirs influenced Mann to revise the character and motivations of Gannett for the polite audiences of conservative New England. By this, the author shows how the biography of Wollstonecraft helped to mold American biographies of women at the turn of the nineteenth century.